ENTREPRENEURSHIP CLINIC FOR FINANCE AND MARKETING: UPAYA PEMBERDAYAAN KELOMPOK USAHA PADA BUMDESA LANGGAM SAKO MENUJU SUSTAINABLE COMPETITIVE ADVANTAGE - Alwie, Alvi Furwanti; Azlina, Nur; Iznillah, Muhammad Luthfi; Taufik, Taufeni; Maulana, Gilang Eka; Ramadhan, Gian Riovi (Jurnal Abdi Insani, 2024)
Entrepreneurship Clinic for Finance and Marketing was conducted as an effort to empower business groups within BUMDesa Langgam Sako to achieve sustainable competitive advantage. In an era of increasing competition, it is essential for rural enterprises to strengthen their production capacity, management, and marketing strategies to maintain business sustainability. Therefore, this training was designed to provide participants with relevant knowledge and skills. The objective of this activity was to enhance the capacity and competitiveness of BUMDesa Langgam Sako's business groups through comprehensive training in production, management, and marketing. The training was held from August 4th to 9th, 2024, at BUMDesa Langgam Sako, Teluk Latak Village, Bengkalis Regency. The training consisted of workshops and interactive classroom sessions. Participants were provided with relevant materials and opportunities to practice the skills they learned. This activity was attended by 30 participants from BUMDesa Langgam Sako’s business units, who showed significant improvement in their understanding of production techniques, business management, and online marketing. Monitoring and evaluation revealed that this training successfully strengthened managerial foundations, improved production standards, and expanded the digital marketing reach of the participants. Participants were also provided with training modules to ensure ongoing understanding. This training was effective in enhancing the capacity of BUMDesa’s enterprises and is expected to provide sustainable impacts on the growth and competitiveness of these business units in the future.